Redesign the 4:2 compressor for partial product reduction - Hussin, R.; Ali Yeon, Md Shakaff; Idris, N.; Zaliman, Sauli; Ismail, R.C.; Kamarudin, A. (International Association of Science and Technology for Development (IASTED) / ACTA Press, 2009)
Link to publisher's homepage at http://www.iasted.org/